2014
DOI: 10.1002/hup.2392
|View full text |Cite
|
Sign up to set email alerts
|

Psychological functioning 1 year after a brief intervention using micronutrients to treat stress and anxiety related to the 2011 Christchurch earthquakes: a naturalistic follow‐up

Abstract: Disaster survivors improve psychologically over time regardless of receiving intervention; however, those taking micronutrients during the acute phase following a disaster show better outcomes, identifying micronutrients as a viable treatment for acute stress following a natural disaster with maintenance of benefits 1 year later. ACTRN 12611000460909

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 40 publications
1
23
0
Order By: Relevance
“…Unfortunately, some concerning evidence suggests that individuals with a history of early trauma may not only exhibit a higher incidence of psychopathology but are also less likely to respond to existing treatments. Research from our laboratory shows that rodents with a history of early-life stress are more vulnerable to fear relapse following extinction (Callaghan & Richardson 2011;Cowan et al 2013), which is in keeping with epidemiological Tx HDAC inhibitors reverse methylation effects & aberrant adult fear learning following MS (Kao et al, 2012) Probiotics reduce corticosterone response to MS and reverse aberrant fear maturation in MS infants (Cowan et al, 2015, Gareau et al, 2007 Early maturation of fear learning/regulation Epigenetic modulation DEVELOPMENT Tx HDAC inhibitors reverse effects of low maternal care in rats (Weaver et al, 2004(Weaver et al, , 2005(Weaver et al, , 2006 Micronutrients reduce PTSD symptoms in earthquake survivors (Rucklidge et al, 2012(Rucklidge et al, , 2014 Probiotics reduce depression in adult MS rats (Desbonnet et al, 2010) Increased incidence of psychopathology Resistance to treatment HPA axis responsivity…”
Section: Traditional Mental Health Treatmentsmentioning
confidence: 66%
“…Unfortunately, some concerning evidence suggests that individuals with a history of early trauma may not only exhibit a higher incidence of psychopathology but are also less likely to respond to existing treatments. Research from our laboratory shows that rodents with a history of early-life stress are more vulnerable to fear relapse following extinction (Callaghan & Richardson 2011;Cowan et al 2013), which is in keeping with epidemiological Tx HDAC inhibitors reverse methylation effects & aberrant adult fear learning following MS (Kao et al, 2012) Probiotics reduce corticosterone response to MS and reverse aberrant fear maturation in MS infants (Cowan et al, 2015, Gareau et al, 2007 Early maturation of fear learning/regulation Epigenetic modulation DEVELOPMENT Tx HDAC inhibitors reverse effects of low maternal care in rats (Weaver et al, 2004(Weaver et al, , 2005(Weaver et al, , 2006 Micronutrients reduce PTSD symptoms in earthquake survivors (Rucklidge et al, 2012(Rucklidge et al, , 2014 Probiotics reduce depression in adult MS rats (Desbonnet et al, 2010) Increased incidence of psychopathology Resistance to treatment HPA axis responsivity…”
Section: Traditional Mental Health Treatmentsmentioning
confidence: 66%
“…Two longer term studies suggest that those who stop consuming the nutrients have poorer psychological outcomes than those who remain on them. 37,38 These studies also reported that the reasons for stopping these formulations related to the number of pills and cost, rather than adverse effects or lack of efficacy. 37,38 Another limitation is that the size of our sample was small and the majority of participants were of NZ European ethnicity and of average SES.…”
Section: Discussionmentioning
confidence: 99%
“…37,38 These studies also reported that the reasons for stopping these formulations related to the number of pills and cost, rather than adverse effects or lack of efficacy. 37,38 Another limitation is that the size of our sample was small and the majority of participants were of NZ European ethnicity and of average SES. We did not have any pregnant or breastfeeding women in the study and caution is advised using nutrients with these populations, although current research in our laboratory is evaluating safety in these populations.…”
Section: Discussionmentioning
confidence: 99%
“…The adverse psychological impact of earthquakes is well documented, 12 13 14 including several studies investigating the effect of the Canterbury earthquakes. 11 18 19 20 21 Given that there are epidemiological data supporting a possible role for vitamin D in the improvement of mental wellbeing, 3 4 5 6 it was plausible that vitamin D supplementation could potentially reduce anxiety or stress or the overall adverse impact of the earthquakes. Of the few randomised controlled trials that have investigated the effect of vitamin D supplementation on mental wellbeing, however, the findings have been mixed.…”
Section: Discussionmentioning
confidence: 99%